Blue, green and red three-primary-color fluorescent carbon dots based on high fluorescence quantum yield and application of blue, green and red three-primary-color fluorescent carbon dots
By using phytic acid and orthophenylenediamine as raw materials, three primary color carbon dots with high fluorescence quantum yields were prepared, which solved the problem of low quantum yields in the prior art and achieved many Efficient preparation and application of chromoluminescent materials.
Patent Information
- Application Number
- CN202411495481.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-25
AI Technical Summary
When preparing multi-color luminescent carbon dots, the existing carbon dot materials have low quantum yields and high requirements for raw material ratio, solvent selection and temperature control, making it difficult to achieve multi-color luminescence with high fluorescence quantum yields.
Phytic acid and orthophenylenediamine are used as raw materials to prepare the primary fluorescent carbon dots of blue, green and red under different proportions and in solvents through solvent thermal reaction, and the raw material ratio and reaction conditions are regulated to improve quantum yield.
The quantum yields reached 19.2%, 68.68% and 60.29% respectively, and the spectrum coverage of the full visible light area was achieved by regulating the carbon dot ratio. It is suitable for light emitting diodes and fluorescent solar energy. Concentrator.
Smart Images

Figure CN119463860A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fluorescent carbon nanomaterials, and relates to fluorescent carbon dots of three primary colors of blue, green and red light with high fluorescence quantum yield, and a preparation method and application thereof. Background Art
[0002] Carbon dots are an emerging type of zero-dimensional fluorescent carbon nanomaterial. Based on the properties of carbon materials and the rich functional groups on the surface, they have the advantages of excellent optical properties, adjustable luminescent color, low toxicity, and good photostability. They are mainly used in cell imaging, anti-counterfeiting, ion detection, optical devices and other fields.
[0003] At present, the preparation method of carbon dots mainly adopts the bottom-up method, which uses small molecules as raw materials and uses the solvent thermal method to carbonize them under high temperature and high pressure to obtain carbon dots. However, this method can only obtain single-color fluorescent carbon dots under most conditions, and the quantum yield is low.
[0004] In recent years, Xiong Huanming's research group has used column chromatography to purify and separate carbon dots synthesized from o-phenylenediamine and urea (Ding H, Yu SB, Wei JS, et al. Full-Color Light-Emitting Carbon Dotswith a Surface-State-Controlled Luminescence Mechanism[J]. ACS Nano , 2016,10: 484-491.), obtained full-spectrum luminescent carbon dots with a maximum quantum yield of 24%; furthermore, his research group also used o-phenylenediamine and L-glutamic acid as raw materials (Ding H, Wei J, Zhang P, et al. Solvent-Controlled Synthesis of Highly Luminescent Carbon Dots with a Wide Color Gamut and Narrowed Emission Peak Widths[J]. Small , 2018, 14: 1800612.), by adjusting the solvent, the full spectrum emission from blue to near-infrared was achieved, and the quantum yield reached up to 54%.
[0005] Wang Liang et al. (Wang L, Li W, Yin L, et al. Full-color fluorescent carbonquantum dots[J]. Science Advances, 2020, 6: eabb6772.) Using o-phenylenediamine and weak acid as raw materials, by changing the type of weak acid and the ratio of weak acid to o-phenylenediamine, full-spectrum luminescent carbon dots with a quantum yield of up to 72% were synthesized.
[0006] However, the luminescence of most carbon dots is controlled by their surface state or carbon core state, which places high demands on the raw materials, solvent selection and temperature control of carbon dot synthesis. How to prepare multi-color luminescent carbon dots with high fluorescence quantum yield by only adjusting the raw material ratio is of great value to improving the optical properties of carbon dots and promoting their application in the industrial production of optical devices.
[0007] In addition, the current fluorescent solar concentrators not only have low absorption efficiency and large reabsorption, but also the commonly used quantum dot materials such as CdSe, CdS, PbS, etc. are easy to deteriorate, and their toxicity has caused environmental and health concerns. In comparison, carbon dots have many advantages such as high stability, high absorption efficiency, and large Stokes shift, and their application in fluorescent solar concentrators has important prospects. Summary of the invention
[0008] The purpose of the present invention is to provide a blue, green and red primary color fluorescent carbon dot and a preparation method thereof based on high fluorescence quantum yield in view of the deficiencies in the prior art, so as to apply the same to light emitting diodes and fluorescent solar concentrators.
[0009] The blue, green and red primary color fluorescent carbon dots with high fluorescence quantum yield described in the present invention are prepared by using phytic acid and o-phenylenediamine as raw materials, dispersing them in a solvent for solvothermal reaction, and adjusting the raw material ratio to obtain blue, green and red primary color fluorescent carbon dots with high fluorescence quantum yield.
[0010] Specifically, when the mass ratio of phytic acid to o-phenylenediamine is (8-20):1, blue light carbon dots can be prepared; when the mass ratio of phytic acid to o-phenylenediamine is (2-5):1, green light carbon dots can be prepared; when the mass ratio of phytic acid to o-phenylenediamine is (0.1-1):1, red light carbon dots can be prepared.
[0011] More specifically, the solvent is at least one of water, ethanol, methanol, N,N-dimethylformamide, dimethyl sulfoxide, and dichloromethane.
[0012] The present invention also provides a specific preparation method of the three-primary-color fluorescent carbon dots, which is to disperse the phytic acid and o-phenylenediamine in different mass ratios in a solvent, place them in a closed high-pressure reactor and heat them to 180-250°C for solvent thermal reaction, filter out the reaction products, and dry them to obtain blue, green and red three-primary-color carbon dots with high fluorescence quantum yield.
[0013] Furthermore, the solvent thermal reaction time is preferably 10 to 34 hours.
[0014] The present invention selects phytic acid and o-phenylenediamine in different mass ratios as raw materials, and prepares blue, green and red primary color fluorescent carbon dots with quantum yields of 19.2%, 68.68% and 60.29% respectively through a one-step solvothermal method, wherein the blue light carbon dots show excitation-dependent characteristics in the solution, and the green light carbon dots and the red light carbon dots show excitation-independent characteristics in the solution.
[0015] The present invention further provides the use of the blue, green and red three primary color fluorescent carbon dots for preparing light emitting diode devices.
[0016] Specifically, the blue, green and red three primary color fluorescent carbon dots are mixed with a polymer solution to prepare a solid luminescent three primary color carbon dot / polymer film, which is used as a fluorescent material and assembled with chips of different excitation wavelengths to prepare a multicolor light emitting diode.
[0017] More specifically, the polymer solution is a solution obtained by dissolving at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polymethyl methacrylate or polysiloxane in a soluble organic solvent.
[0018] Among them, in the chips with different excitation wavelengths, the excitation wavelength can be any one of 360nm, 380nm, 400nm, 420nm, 440nm, and 460nm.
[0019] Based on the excitation-dependent characteristics of blue carbon dots, the emission colors of blue carbon dots are different when using chips with different excitation wavelengths. For example, when using a chip with an excitation wavelength of 360nm, it corresponds to an emission of 430nm. Correspondingly, 380nm, 400nm, 420nm, 440nm, and 460nm chips correspond to 450nm, 465nm, 490nm, 520nm, and 540nm emissions, respectively.
[0020] Furthermore, due to the significant excitation-dependent characteristics of the blue carbon dots, it is possible to use them to prepare white light LED devices. The present invention adjusts the ratio of blue carbon dots in the solid-state luminescent three primary colors carbon dots / polymer film so that the luminescence spectrum can cover the entire visible light region, and can not only prepare pure color blue LED devices, but also realize the preparation of cold white LEDs, standard white LEDs and warm white LEDs.
[0021] Based on the independent excitation characteristics of green carbon dots and red carbon dots, the luminescent colors obtained when using chips with different excitation wavelengths are the same, where green carbon dots emit 500nm green light and red carbon dots emit 600nm red light. Therefore, the present invention preferably uses conventional 360nm ultraviolet chips to prepare green and red LED devices.
[0022] Furthermore, the present invention also provides the use of the blue, green and red three primary color fluorescent carbon dots for preparing a multicolor fluorescent solar concentrator.
[0023] Specifically, the blue, green and red three primary color fluorescent carbon dots are mixed with a polymer solution to obtain a mixed solution, which is coated on a glass surface and coupled with a solar cell to prepare a fluorescent solar concentrator.
[0024] More specifically, the polymer solution is a solution obtained by dissolving at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polymethyl methacrylate or polysiloxane in a soluble organic solvent.
[0025] The fluorescent solar concentrator prepared by the present invention has a maximum absorption efficiency of 23.3% for the sun, and its larger Stokes shift can also reduce the reabsorption efficiency of the fluorescent solar concentrator. Finally, the photoelectric conversion efficiency of the single-sided coupled silicon-based solar cell of the fluorescent solar concentrator can reach 0.3%.
[0026] However, due to the significant excitation-dependent characteristics of blue light carbon dots, a large amount of reabsorption occurs, resulting in a very low photoelectric conversion efficiency of the fluorescent solar concentrator prepared by blue light carbon dots. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a transmission electron microscope morphology image of the blue light carbon dots prepared in Example 1.
[0028] Figure 2 This is the fluorescence spectrum of the blue light carbon dots in Example 1.
[0029] Figure 3 This is the luminescence spectrum of the cold white light LED device prepared in Example 2.
[0030] Figure 4 3 is the color coordinate diagram of the cold white light LED device of Example 2.
[0031] Figure 5 This is the luminescence spectrum of the standard white light LED device prepared in Example 3.
[0032] Figure 6 3 is the color coordinate diagram of the standard white light LED device of Example 3.
[0033] Figure 7 This is the luminescence spectrum of the warm white light LED device prepared in Example 4.
[0034] Figure 8 3 is the color coordinate diagram of the warm white light LED device of Example 4.
[0035] Fig. 9This is the luminescence spectrum of the blue light LED device prepared in Example 5.
[0036] Fig.10 This is the absorption efficiency spectrum of the blue light solar concentrator prepared in Example 6.
[0037] Fig.11 This is a transmission electron microscope morphology image of the green light carbon dots prepared in Example 7.
[0038] Fig.12 This is the fluorescence spectrum of the green light carbon dots in Example 7.
[0039] Fig.13 This is the luminescence spectrum of the green light LED device prepared in Example 8.
[0040] Fig.14 This is the absorption efficiency spectrum of the green light solar concentrator prepared in Example 9.
[0041] Fig.15 This is a transmission electron microscope morphology image of the red light carbon dots prepared in Example 10.
[0042] Fig.16 It is the fluorescence spectrum of the red light carbon dots in Example 11.
[0043] Fig.17 This is the luminescence spectrum of the red light LED device prepared in Example 12.
[0044] Fig.18 This is the absorption efficiency spectrum of the red light solar concentrator prepared in Example 13. Implementation
[0045] The specific implementation of the present invention is further described in detail below in conjunction with the accompanying drawings and examples. The following examples are only used to more clearly illustrate the technical solution of the present invention so that those skilled in the art can well understand and utilize the present invention, rather than limiting the scope of protection of the present invention.
[0046] The production processes, experimental methods or detection methods involved in the embodiments and comparative examples of the present invention are all conventional methods in the prior art unless otherwise specified, and their names and / or abbreviations are all conventional names in the field and are very clear and unambiguous in the relevant application fields. Technicians in the field can understand the conventional process steps based on the names and apply the corresponding equipment to implement them according to conventional conditions or the conditions recommended by the manufacturer.
[0047] The various instruments, equipment, raw materials or reagents used in the embodiments of the present invention are not particularly limited in terms of their sources, and are all conventional products that can be purchased through regular commercial channels, or can be prepared according to conventional methods well known to those skilled in the art. Example
[0048] Example 1
[0049] 2500 mg of phytic acid and 180 mg of o-phenylenediamine were weighed, added to 20 mL of ethanol, placed in a polytetrafluoroethylene-lined stainless steel autoclave, and subjected to solvent thermal treatment at 230°C for 22 h. After the reaction was completed, the mixture was naturally cooled to room temperature in air to obtain a crude carbon dot solution.
[0050] The obtained crude carbon dot solution was filtered with a 0.22 μm syringe filter, and the filtrate was rotary evaporated and vacuum dried to obtain solid blue light carbon dots.
[0051] The blue light carbon dots prepared as above were dissolved in DMSO solution to obtain a blue light carbon dots solution, and its physical properties and luminescence performance were characterized.
[0052] from Figure 1 From the transmission electron microscopy morphology, it can be seen that the blue light carbon dots are spherical in shape, without obvious aggregation, with a narrow particle size distribution range and an average particle size of 5.79nm.
[0053] Figure 2 The fluorescence spectrum of the blue light carbon dot solution is shown in FIG. 4 . When the carbon dot solution is excited with different excitation wavelengths, the emission peak positions of the carbon dot solution are different, indicating that the blue light carbon dot solution has an excitation-dependent characteristic, and its optimal excitation wavelength is at 360 nm, and the optimal emission wavelength under 360 nm excitation light is 430 nm.
[0054] By detecting the number of photons emitted by the carbon dot solution and the number of photons absorbed by the 360nm excitation light, the quantum yield of the blue light carbon dots was calculated to be 19.2%.
[0055] Example 2
[0056] 5 mg of the blue light carbon dots prepared in Example 1 were weighed and dissolved in 10 mL of 120 mg / mL polyvinyl pyrrolidone ethanol solution, and stirred at 500 r / min for 5 min to obtain a blue light carbon dots / polyvinyl pyrrolidone complex mixed solution.
[0057] Take 30 μL of the mixed solution, drop it onto the LED lamp cap, dry it, and then repeat the dropping for a total of 90 μL. After complete drying, a blue light carbon dot / polyvinyl pyrrolidone composite fluorescent film is obtained.
[0058] The lamp cap with the fluorescent film is covered on the LED chip with an excitation wavelength of 360nm to assemble a cold white light LED device.
[0059] Figure 3 The luminescence spectrum of the above-mentioned cold white light LED device is given. Under the excitation of a 360nm excitation chip, its luminescence spectrum covers most of the visible light region.
[0060] Through the above luminescence spectrum, the CIE coordinates of the device can be calculated to be (0.332, 0.340), the color temperature is 5493K, and it belongs to cold white light. Figure 4 As shown in the figure, the device has a higher color rendering index of 98.
[0061] Example 3
[0062] 6 mg of the blue light carbon dots prepared in Example 1 were weighed and dissolved in 10 mL of 120 mg / mL polyvinyl pyrrolidone ethanol solution, and stirred at 500 r / min for 5 min to obtain a blue light carbon dots / polyvinyl pyrrolidone complex mixed solution.
[0063] Take 30 μL of the mixed solution, drop it onto the LED lamp cap, dry it, and then repeat the dropping for a total of 90 μL. After complete drying, a blue light carbon dot / polyvinyl pyrrolidone composite fluorescent film is obtained.
[0064] The lamp cap with the fluorescent film is covered on the LED chip with an excitation wavelength of 360nm to assemble a standard white light LED device.
[0065] Figure 5 In the above standard white light LED device emission spectrum diagram, the emission spectrum covers most of the visible light region when excited by the 360nm excitation chip. The CIE coordinates of the device are calculated to be (0.359, 0.364), the color temperature is 4548K, which belongs to standard white light, and the color rendering index is 97. Figure 6 shown.
[0066] Example 4
[0067] 10 mg of the blue light carbon dots prepared in Example 1 was weighed and dissolved in 10 mL of 120 mg / mL polyvinyl pyrrolidone ethanol solution, and stirred at 500 r / min for 5 min to obtain a blue light carbon dots / polyvinyl pyrrolidone complex mixed solution.
[0068] Take 30 μL of the mixed solution, drop it onto the LED lamp cap, dry it, and then repeat the dropping for a total of 90 μL. After complete drying, a blue light carbon dot / polyvinyl pyrrolidone composite fluorescent film is obtained.
[0069] The lamp cap with the fluorescent film is covered on the LED chip with an excitation wavelength of 360nm to assemble a warm white light LED device.
[0070] Figure 7 In the above-mentioned warm white LED device emission spectrum diagram, the emission spectrum covers most of the visible light region through 360nm excitation chip excitation. The CIE coordinates of the device are calculated to be (0.427, 0.388), the color temperature is 3033K, which belongs to warm white light, and the color rendering index is 97. Figure 8 shown.
[0071] Example 5
[0072] 0.5 mg of the blue light carbon dots prepared in Example 1 was weighed and dissolved in 10 mL of 120 mg / mL polyvinyl pyrrolidone ethanol solution, and stirred at 500 r / min for 5 min to obtain a blue light carbon dots / polyvinyl pyrrolidone complex mixed solution.
[0073] Take 30 μL of the mixed solution, drop it onto the LED lamp cap, dry it, and then repeat the dropping for a total of 90 μL. After complete drying, a blue light carbon dot / polyvinyl pyrrolidone composite fluorescent film is obtained.
[0074] The lamp cap with the fluorescent film is covered on the LED chip with an excitation wavelength of 360nm to assemble a blue light LED device. Fig. 9 The device luminescence spectrum shows that it has blue light emission.
[0075] Example 6
[0076] 5 mg of the blue light carbon dots prepared in Example 1 were weighed and dissolved in 10 mL of 120 mg / mL polyvinyl pyrrolidone ethanol solution, and stirred at 500 r / min for 5 min to obtain a blue light carbon dots / polyvinyl pyrrolidone complex mixed solution.
[0077] Take 3 mL of the mixed solution and drop it onto the surface of 5 cm×5 cm ultra-white glass, dry it in air, and couple the solar cell to the side of the ultra-white glass to obtain a blue light solar concentrator.
[0078] Fig.10 The absorption efficiency spectrum of the prepared blue light solar concentrator is given. The red line in the figure represents the absorption spectrum of the carbon dot polymer material, and the light blue background is the solar spectrum. The blue curve is obtained by multiplying these two curves. After integrating it, it is compared with the integrated area of the solar spectrum. The ratio is taken as the absorption efficiency of the material, which is 2.4%.
[0079] Example 7
[0080] 540 mg of phytic acid and 180 mg of o-phenylenediamine were weighed, added to 20 mL of ethanol, placed in a polytetrafluoroethylene-lined stainless steel autoclave, and solvent thermally treated at 230°C for 22 h. After the reaction was completed, the mixture was naturally cooled to room temperature in air to obtain a crude carbon dot solution.
[0081] The obtained crude carbon dot solution was filtered with a 0.22 μm syringe filter, and the filtrate was rotary evaporated and vacuum dried to obtain solid green carbon dots.
[0082] The green carbon dots prepared as above were dissolved in DMSO solution to obtain a green carbon dots solution, and its physical properties and luminescence performance were characterized.
[0083] Fig.11 In the transmission electron microscope morphology image, the green light carbon dots are spherical in shape, with no obvious aggregation, a narrow particle size distribution range, and an average particle size of 4.69nm.
[0084] Fig.12 In the fluorescence spectrum diagram, the emission peak position is the same when the green light carbon dot solution is excited with different excitation wavelengths, indicating that the green light carbon dot solution has the characteristics of excitation independence, and its optimal excitation wavelength is at 380nm. The optimal emission wavelength under 380nm excitation light is 500nm, and the quantum yield is 68.68%.
[0085] Example 8
[0086] 5 mg of the green carbon dots prepared in Example 7 were weighed and dissolved in 10 mL of 120 mg / mL polyvinyl pyrrolidone ethanol solution, and stirred at 500 r / min for 5 min to obtain a green carbon dots / polyvinyl pyrrolidone complex mixed solution.
[0087] Take 30 μL of the mixed solution, drop it onto the LED lamp cap, dry it, and then repeat the dropping for a total of 90 μL. After complete drying, a green carbon dot / polyvinyl pyrrolidone composite fluorescent film is obtained.
[0088] The lamp cap with the fluorescent film is covered on the LED chip with an excitation wavelength of 360nm to assemble a green light LED device. Fig.13 The device luminescence spectrum shows that it has green light emission.
[0089] Example 9
[0090] 5 mg of the green carbon dots prepared in Example 7 were weighed and dissolved in 10 mL of 120 mg / mL polyvinyl pyrrolidone ethanol solution, and stirred at 500 r / min for 5 min to obtain a green carbon dots / polyvinyl pyrrolidone complex mixed solution.
[0091] Take 3 mL of the mixed solution and drop it onto the surface of 5 cm×5 cm ultra-white glass, dry it in air, and couple the solar cell to the side of the ultra-white glass to obtain a green light solar concentrator.
[0092] Fig.14 In the green light solar concentrator absorption efficiency spectrum, the spectrum obtained by multiplying the absorption spectrum of the carbon dot polymer material and the solar energy spectrum is integrated, and then ratioed with the integral of the solar energy spectrum, and the absorption efficiency of the material is obtained to be 6.3%.
[0093] Example 10
[0094] 60 mg of phytic acid and 180 mg of o-phenylenediamine were weighed, added to 20 mL of ethanol, placed in a polytetrafluoroethylene-lined stainless steel autoclave, and solvent thermally treated at 230°C for 22 h. After the reaction was completed, the mixture was naturally cooled to room temperature in air to obtain a crude carbon dot solution.
[0095] The obtained crude carbon dot solution was filtered with a 0.22 μm syringe filter, the filtrate was evaporated to remove part of the solvent, and then dropped into 100 mL of water to obtain a turbid solution, which was centrifuged at 10,000 rpm for 10 min, repeated twice, and the upper layer of the solution was discarded and dried to obtain a red-light carbon dot black powder.
[0096] The red-light-emitting carbon dots prepared as above were dissolved in DMSO solution to obtain a red-light-emitting carbon dots solution, and its physical properties and luminescence performance were characterized.
[0097] Fig.15 In the transmission electron microscopy morphology of the red light carbon dots solution, the red light carbon dots are spherical in shape, without obvious aggregation, with a narrow particle size distribution range and an average particle size of 7.65nm.
[0098] Fig.16 Figure 3 is the fluorescence spectrum of the red light carbon dot solution. When the carbon dot solution is excited with different excitation wavelengths, the emission peak position is the same, indicating that the red light carbon dot solution has the characteristic of excitation independence. The optimal excitation wavelength is at 520nm, and the optimal emission wavelength under 520nm excitation light is 593nm, with a quantum yield of 60.29%.
[0099] Embodiment 11
[0100] 5 mg of the red-light carbon dots prepared in Example 10 were weighed and dissolved in 10 mL of 120 mg / mL polyvinyl pyrrolidone ethanol solution, and stirred at 500 r / min for 5 min to obtain a red-light carbon dots / polyvinyl pyrrolidone complex mixed solution.
[0101] Take 30 μL of the mixed solution, drop it onto the LED lamp cap, dry it, and then repeat the dropping, add 90 μL in total, and after complete drying, obtain a red carbon dot / polyvinyl pyrrolidone composite fluorescent film.
[0102] The lamp cap with the fluorescent film is covered on the LED chip with an excitation wavelength of 360nm to assemble a red light LED device. Fig.17 The device luminescence spectrum shows that it has red light emission.
[0103] Example 12
[0104] 5 mg of the red-light carbon dots prepared in Example 7 were weighed and dissolved in 10 mL of a 120 mg / mL polymethyl methacrylate DMF solution, and stirred at 500 r / min for 5 min to obtain a red-light carbon dots / polymethyl methacrylate composite mixed solution.
[0105] Take 3 mL of the mixed solution and drop it onto the surface of 5 cm×5 cm ultra-white glass, dry it in air, and couple the solar cell to the side of the ultra-white glass to obtain a red light solar concentrator.
[0106] Fig.18 In the red light solar concentrator absorption efficiency spectrum, the spectrum obtained by multiplying the absorption spectrum of the carbon dot polymer material with the solar energy spectrum is integrated, and the ratio of the integral of the solar energy spectrum gives a material absorption efficiency of 23.3%.
[0107] The above embodiments of the present invention do not describe all the details in detail, nor limit the present invention to the above embodiments. Various changes, modifications, substitutions and variations made by ordinary technicians in this field without departing from the principles and purpose of the present invention should be included in the protection scope of the present invention.
Claims
1. A blue, green and red primary color fluorescent carbon dot based on high fluorescence quantum yield, which is prepared by dispersing phytic acid and o-phenylenediamine in a solvent for solvothermal reaction, and adjusting the ratio of the raw materials to obtain blue, green and red primary color carbon dots with high fluorescence quantum yield, wherein: When the mass ratio of phytic acid to o-phenylenediamine is (8-20):1, blue light carbon dots are obtained; When the mass ratio of phytic acid to o-phenylenediamine is (2-5):1, green carbon dots are obtained; When the mass ratio of phytic acid to o-phenylenediamine is (0.1-1):1, red-emitting carbon dots are obtained.
2. The blue, green and red primary color fluorescent carbon dots based on high fluorescence quantum yield according to claim 1, characterized in that The solvent is at least one of water, ethanol, methanol, N,N-dimethylformamide, dimethyl sulfoxide and dichloromethane.
3. The method for preparing the blue, green and red primary color fluorescent carbon dots according to claim 1 is to disperse the phytic acid and o-phenylenediamine in different mass ratios in a solvent, and perform a solvothermal reaction at 180-250° C. to prepare blue, green and red primary color carbon dots with high fluorescence quantum yield.
4. The method for preparing blue, green and red primary color fluorescent carbon dots according to claim 3, characterized in that The solvent thermal reaction time is 10 to 34 hours.
5. Use of the blue, green and red primary color fluorescent carbon dots according to claim 1 in the preparation of light emitting diode devices.
6. The application according to claim 5 is to prepare a solid-state luminescent three-primary-color carbon dot / polymer film by mixing the blue, green and red three-primary-color fluorescent carbon dots with a polymer solution, and assemble the film with chips of different excitation wavelengths as fluorescent materials to prepare a multicolor light-emitting diode.
7. The use according to claim 6, characterized in that The excitation wavelength of the chip is any one of 360nm, 380nm, 400nm, 420nm, 440nm, and 460nm.
8. Use of the blue, green and red primary color fluorescent carbon dots according to claim 1 in the preparation of multicolor fluorescent solar concentrators.
9. The use according to claim 8 is to mix the blue, green and red primary fluorescent carbon dots with a polymer solution to obtain a mixed solution, coat the mixed solution on a glass surface and couple it with a solar cell to prepare a fluorescent solar concentrator.
10. The use according to claim 6 or 9, characterized in that The polymer solution is a solution obtained by dissolving at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polymethyl methacrylate or polysiloxane in a soluble organic solvent.
Citation Information
Patent Citations
High-quantum-yield eigenstate-fluorescence-adjustable carbon dot and preparing method and application thereof
CN106566538A
Controllable synthesis method of near-full spectrum emission carbon quantum dots
CN110184050A
Green fluorescent carbon quantum dot with high yield and high fluorescent quantum yield, and preparation method thereof
CN110562957A
Method for preparing full-spectrum fluorescent carbon dots by using one-pot method
CN110982517A
Preparation method of carbon quantum dot-water-soluble polyurethane solution
CN113045978A